Milky white urine: a look into the differentials - Manappallil, Robin George (International Journal of Advances in Medicine, 2016)
Urine analysis is one the simplest means to evaluate renal diseases. Physical and chemical characteristics and microscopic examination provide information regarding the status of kidneys and urinary tracts. The colour, odour, turbidity and specific gravity are the parameters considered under physical examination of urine. This is a case of a 40 year old diabetic lady, who presented with history of dysuria and low grade fever. Her urine was milky white in colour, usually seen in chyluria. On evaluation, she was found to be in sepsis due to urinary tract infection, and her urine analysis was suggestive of pyuria. This form of white urine has rarely been reported with pyuria. This report also looks into the differential diagnosis of white coloured urine.